Effectiveness of Screens Shading Opaque Facades in Terms of Building Thermal Modernisation - Siewczyńska, Monika; Ksit, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Screens used in modernizations of buildings to diversify the facade also provide shade on the walls. The article presents a comparison of the effectiveness of shades with different degrees of shading in terms of energy savings. On summer days, especially when there is a lot of sunlight and air temperatures are above 30°C, the covers reduce the temperature on the outer surface of the wall and, as a result, improve the microclimate of the rooms. Lower temperatures result in less heat accumulated during the day. The results were compared for various masonry materials. Less heat energy accumulated in the wall reduces the energy demand to cool the internal air. Energy savings were estimated over 50 years of building use. A method was proposed to quickly compare the effectiveness of the different shading shields.
Keywords: shading; sunny facades; heat accumulation; energy savings; renovation; thermal modernisation